The potential effect of natural antioxidants on endothelial dysfunction associated with arterial hypertension - Caminiti, Rosamaria; Carresi, Cristina; Mollace, Rocco; Macrì, Roberta; Scarano, Federica; Oppedisano, Francesca; Maiuolo, Jessica; Serra, Maria; Ruga, Stefano; Nucera, Saverio; Tavernese, Annamaria; Gliozzi, Micaela; et al. (Frontiers in Cardiovascular Medicine, 2024)
Arterial hypertension represents a leading cause of cardiovascular morbidity and mortality worldwide, and the identification of effective solutions for treating the early stages of elevated blood pressure (BP) is still a relevant issue for cardiovascular risk prevention. The pathophysiological basis for the occurrence of elevated BP and the onset of arterial hypertension have been widely studied in recent years. In addition, consistent progress in the development of novel, powerful, antihypertensive drugs and their appropriate applications in controlling BP have increased our potential for successfully managing disease states characterized by abnormal blood pressure. However, the mechanisms responsible for the disruption of endogenous mechanisms contributing to the maintenance of BP within a normal range are yet to be fully clarified. Recently, evidence has shown that several natural antioxidants containing active ingredients originating from natural plant extracts, used alone or in combination, may represent a valid solution for counteracting the development of arterial hypertension. In particular, there is evidence to show that natural antioxidants may enhance the viability of endothelial cells undergoing oxidative damage, an effect that could play a crucial role in the pathophysiological events accompanying the early stages of arterial hypertension. The present review aims to reassess the role of oxidative stress on endothelial dysfunction in the onset and progression of arterial hypertension and that of natural antioxidants in covering several unmet needs in the treatment of such diseases.